2008
DOI: 10.1021/jf801744r
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Human HepG2 Cells against Oxidative Stress by Cocoa Phenolic Extract

Abstract: Cocoa is a rich source of flavanols and procyanidin oligomers with antioxidative properties, providing protection against oxidation and nitration. The present study investigated the potential protective effect of a polyphenolic extract from cocoa on cell viability and antioxidant defenses of cultured human HepG2 cells submitted to oxidative stress induced by tert-butylhydroperoxide (t-BOOH). Pretreatment of cells with 0.05-50 µg/mL of cocoa polyphenolic extract (CPE) for 2 or 20 h completely prevented cell dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
111
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 108 publications
(130 citation statements)
references
References 58 publications
17
111
0
2
Order By: Relevance
“…Soluble polyphenols were extracted by sequentially washing 1 g of sample with 40 mL of 16 mM hydrochloric acid in 50 % aqueous methanol (50:50, v/v, 1 hour at room temperature, constant shaking) and 40 mL of acetone-water (70:30, v/v, 1 hour room temperature, constant shaking) in 50 mL centrifuge tubes [17]. After centrifugation (15min, 3000 g), supernatants from each extraction step were combined and made up to 100 mL.…”
Section: Cocoa Polyphenol Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soluble polyphenols were extracted by sequentially washing 1 g of sample with 40 mL of 16 mM hydrochloric acid in 50 % aqueous methanol (50:50, v/v, 1 hour at room temperature, constant shaking) and 40 mL of acetone-water (70:30, v/v, 1 hour room temperature, constant shaking) in 50 mL centrifuge tubes [17]. After centrifugation (15min, 3000 g), supernatants from each extraction step were combined and made up to 100 mL.…”
Section: Cocoa Polyphenol Extractionmentioning
confidence: 99%
“…Thus, they can be considered as dietary antioxidants and as natural products with beneficial properties. Cocoa polyphenols have shown to exert their protective action as reducing agents by improving antioxidant defences through the induction of antioxidant and phase II enzymes [17] and also through its ability to modulate certain signalling pathways involved in cell survival and death [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Flavanols EC, ECG and PB2 possess a well characterized in vitro antioxidant activity, and recent studies have shown that these catechins are effective free radical scavengers and interfere with the oxidative/antioxidative potential of hepatic (Coyle et al, 2008;Chen et al, 2002;Granado-Serrano et al, 2007, 2009bMartin et al, 2008) and colonic cells (Rodríguez-Ramiro et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Induction of antioxidant/detoxifying enzymes as well as glutathione (GSH) levels provide significant biological mechanisms for protection against toxic effects of endogenous reactive oxygen species (ROS) and exogenous carcinogens and/or their reactive intermediates (GranadoSerrano et al, 2007(GranadoSerrano et al, , 2009bMartin et al, 2008Martin et al, , 2010Rodríguez-Ramiro et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation